Ох, социализм, социализм!.: [сборник] / Андрей Нуйкин - Нуйкин Андрей Александрович (Библиотека "Огонек", 1990)
Экземпляры: КХ (20101028) / Инвентарный номер: 0287380 / Цена: 0.15 / Сис.шифр: 66.3(2) / Авт.знак: Н 88 / ГРНТИ: 03 / ББК: 63.3(2)634